On Two Sided -n-Derivations in Prime near – Rings - H. Majeed, Abdul Rahman; F. Adhab, Enaam (Iraqi Journal of Science, 2023)
In this paper, we investigate prime near – rings with two sided α-n-derivationssatisfying certain differential identities. Consequently, some well-known resultshave been generalized. Moreover, an example proving the necessity of the primnesshypothesis is given.